Evaluation of Pragmatic Telehealth Physical Therapy Implementation During the COVID-19 Pandemic. Issue 1 (19th October 2020) - Miller, Matthew J; Pak, Sang S; Keller, Daniel R; Barnes, Deborah E
Abstract: Objective: The objective was to evaluate implementation of telehealth physical therapy in response to COVID-19 and identify implementation strategies to maintain and scale up telehealth physical therapy within a large urban academic medical center. Methods: The Reach Effectiveness Adoption Implementation Maintenance (RE-AIM) framework was used to evaluate telehealth physical therapy implementation. Patient-level data were extracted from electronic medical records between March 16, 2020, and May 16, 2020 (implementation phase). Reach was defined as the proportion of physical therapy sessions completed via telehealth. Effectiveness was assessed using a patient-reported satisfaction survey with a 5-point Likert scale. Adoption was defined as the proportion of physical therapists who used telehealth. Implementation was assessed through qualitative analysis of patient and clinician perspectives to identify emergent themes, retrospectively classify strategies used during the implementation phase, and prospectively identify evidence-based strategies to increase telehealth maintenance and scale-up. Maintenance of telehealth was defined as the proportion of patients who indicated they would attend another telehealth session. Results: There were 4548 physical therapy sessions provided by 40 therapists from March 22, 2020, to May 16, 2020, of which 3883 (85%) were telehealth. Ninety-four percent of patients were satisfied. All physical therapists (100%) used telehealth technology at least once. Retrospectively classified and prospectively identified evidence-based strategies were organized into 5 qualitative themes that supported implementation: organizational factors (policies, preexisting partnerships), engaging external stakeholders (satisfaction survey), champions (clinician leaders), clinician education (dynamic, ongoing training), and process (promote adaptability, small tests of change). Ninety-two percent of patients reported they would attend another telehealth session. Conclusion: Findings from this study suggest that implementation of telehealth physical therapy during the COVID-19 pandemic was feasible and acceptable in this setting. Impact: These results can be used to guide future health policy, quality improvement, and implementation science initiatives to expand the use and study of telehealth for physical therapy.